Some Basic Issues in Labour — Management Arbitration - Chartier, Roger (Relations industrielles / Industrial Relations, 1962)
SummaryThis article is an attempt at probing into the fundamentals of arbitration. It deals with the NATURE and SCOPE of the process of arbitration seen as an extension and an ingredient of collective bargaining, as well as a substitute for strike action. It also analyzes some of its essential PURPOSES, FUNCTIONS, and PREREQUISITES in a free society. It examines the MANAGEMENT-RIGHTS ISSUE in terms of the SPECIFIC FUNCTION OF MANAGEMENT. It then sets EQUITY and PAST PRACTICE against the language of the agreement. And finally, it briefly defines the ROLE OF THE ARBITRATOR and describes SOME RECURRENT DIFFICULTIES which threaten to bog the arbitration process.